Measuring financial sector efficiency in China: A study based on an enhanced neoclassical production function. - Chuanzhen Zheng; Yuan Shan (PLoS ONE)
This paper develops an approach for quantitatively assessing financial sector efficiency of a nation (hereinafter referred to as financial efficiency). Drawing upon the principles of general equilibrium theory, we establish a direct and strong association between the financial sector and the real sector by improving the neoclassical production function, indirectly unveiling insights into financial efficiency through the allocation structure of marginal capital output. We use a two-stage semiparametric estimation method to determine the structural parameters of the production function in the calculation of financial efficiency. The values of financial efficiency for China, spanning the years 1997-2018, exhibit a distinct pattern of initially increasing, followed by a decline, and subsequent resurgence, culminating in the highest recorded value in 2008. Prior to 2015, the financial efficiency closely mirrored the trajectories of total factor productivity (TFP) and GDP growth rate. However, post-2015, we observe a discernible deviation in the trend of financial efficiency from these two economic indicators. These results can be verified by external empirical facts and evidence.